2005
DOI: 10.1002/gene.20098
|View full text |Cite
|
Sign up to set email alerts
|

Cre-mediated recombination in cell lineages that express the progesterone receptor

Abstract: Using gene-targeting methods, a progesterone receptor Cre knockin (PR-Cre) mouse was generated in which Cre recombinase was inserted into exon 1 of the PR gene. The insertion positions the Cre gene downstream (and under the specific control) of the endogenous PR promoter. As for heterozygotes for the progesterone receptor knockout (PRKO) mutation, mice heterozygous for the Cre knockin insertion are phenotypically indistinguishable from wildtype. Crossing the PR-Cre with the ROSA26R reporter revealed that Cre e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
413
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(422 citation statements)
references
References 17 publications
9
413
0
Order By: Relevance
“…Because the systemic Rac1 null mice are embryonic lethal owing to gastrulation defects, 24 to analyze the pathophysiological significance of Rac1 in early pregnancy events, we next used a progesterone receptor (Pgr)-driven Cre (Pgr cre/+ ) mouse model crossed with Rac1 floxed (Rac1 f/f ) mice to achieve uterine-selective deletion of Rac1. [25][26][27] As shown in To ascertain the stage-specific causes accounting for this obvious infertility, we subsequently analyzed the implantation status in mice missing uterine Rac1. Although all Rac1 f/f mice tested showed normal embryo implantation on day 5 morning (Figure 2j).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the systemic Rac1 null mice are embryonic lethal owing to gastrulation defects, 24 to analyze the pathophysiological significance of Rac1 in early pregnancy events, we next used a progesterone receptor (Pgr)-driven Cre (Pgr cre/+ ) mouse model crossed with Rac1 floxed (Rac1 f/f ) mice to achieve uterine-selective deletion of Rac1. [25][26][27] As shown in To ascertain the stage-specific causes accounting for this obvious infertility, we subsequently analyzed the implantation status in mice missing uterine Rac1. Although all Rac1 f/f mice tested showed normal embryo implantation on day 5 morning (Figure 2j).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Uterine-specific mutant mice were generated by crossing Rac1 f/f mice with Pgr Cre/+ mice. 25 All mice were housed in the animal care facility of the Institute of Zoology, Chinese Academy of Sciences, according to the institutional guidelines for the care and use of laboratory animals. Female mice were mated with fertile wild-type males to induce pregnancy (vaginal plug = day 1 of pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…To effectively investigate the role of Mig-6 in the regulation of uterine function and the response to hormonal stimulation, we generated a Mig-6 conditional null allele, the Mig-6 flox allele (Mig-6 f/f ) (33). Mig-6 f/f mice were bred to PR Cre (34) mice to generate conditional Mig-6 ablation (PR cre/ϩ Mig-6 f/f ; Mig-6 d/d ) in the reproductive tract. Significant morphological differences in the uteri of Mig-6 d/d and Mig-6 f/f were not observed at 2 months of age.…”
Section: The Epithelial Hyperplastic Effect In Mice With Conditional mentioning
confidence: 99%
“…Mig-6 d/d mice were completely infertile (Table S3). Since the PR Cre mouse shows Cre recombinase activity in the pituitary, ovary, uterus, and mammary gland, the cause of infertility in these mice may be the result of a defect in any of these tissues (34 Thus, to determine if the infertility was in part because of loss of the ability of the uterus to support implantation, we investigated the ability of the uterus to undergo a decidual reaction. Ovariectomized female Mig-6 f/f and Mig-6 d/d mice (n ϭ 3) were treated with hormones and the uterus was mechanically stimulated to mimic the signaling of the embryo at implantation and to induce decidualization.…”
Section: The Epithelial Hyperplastic Effect In Mice With Conditional mentioning
confidence: 99%
“…These systems fulfill the purpose of generating somatic mutations of a target gene at a given time during the animal's life-span and in a specific cell type. In this respect, there are few studies that have shown Cremediated gene recombination in uterine cells (Jamin et al, 2003;Soyal et al, 2005;Wen et al, 2003). For example, a progesterone receptor Cre (PR-Cre) knockin mouse line has been shown to be able to target various progesterone-responsive tissues including the uterus, ovary, oviduct, pituitary gland, and mammary gland (Soyal et al, 2005).…”
mentioning
confidence: 99%